2016
DOI: 10.15252/embr.201642544
|View full text |Cite
|
Sign up to set email alerts
|

The cohesin REC8 prevents illegitimate inter‐sister synaptonemal complex assembly

Abstract: During meiosis, a specialized chromosome structure is assembled to promote pairing/ synapsis of homologous chromosomes and meiotic recombination, a process yielding chiasmata between homologs to ensure accurate segregation. Meiosis-specific cohesin complexes mediating sister chromatid cohesion play pivotal roles in almost all these events, including synaptonemal complex (SC) formation. In this issue of EMBO Reports, Agostinho and colleagues have examined chromosome axes and SC structures by taking advantage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…In Rec8 KOs, however, the entire length of the chromosome axis becomes two separate SYCP3‐labeled structures, despite the fully localized RAD21L‐cohesin along the sister chromatid axes (Ishiguro et al., ; Xu et al., ). Similar to the observation in Rec8 KOs, super‐resolution microscopic analyses showed that the chromosome axis is regionally separated in hypomorphic Stag3 mutants and Smc1 β KOs, in which REC8‐cohesin levels are partly reduced (Agostinho, Manneberg, Schendel, Hernandez‐Hernandez, & Kouznetsova, ; Fukuda et al., ; Ishiguro & Watanabe, ). Notably, illegitimate SCs are assembled between sister chromatids at the REC8 free “axial opening” regions in these mutants (Agostinho et al., ; Ishiguro & Watanabe, ), as has also been shown in Rec8 KOs (Bannister et al., ; Xu et al., ).…”
Section: Sister Chromatid Cohesion During Meiosissupporting
confidence: 52%
See 1 more Smart Citation
“…In Rec8 KOs, however, the entire length of the chromosome axis becomes two separate SYCP3‐labeled structures, despite the fully localized RAD21L‐cohesin along the sister chromatid axes (Ishiguro et al., ; Xu et al., ). Similar to the observation in Rec8 KOs, super‐resolution microscopic analyses showed that the chromosome axis is regionally separated in hypomorphic Stag3 mutants and Smc1 β KOs, in which REC8‐cohesin levels are partly reduced (Agostinho, Manneberg, Schendel, Hernandez‐Hernandez, & Kouznetsova, ; Fukuda et al., ; Ishiguro & Watanabe, ). Notably, illegitimate SCs are assembled between sister chromatids at the REC8 free “axial opening” regions in these mutants (Agostinho et al., ; Ishiguro & Watanabe, ), as has also been shown in Rec8 KOs (Bannister et al., ; Xu et al., ).…”
Section: Sister Chromatid Cohesion During Meiosissupporting
confidence: 52%
“…Similar to the observation in Rec8 KOs, super‐resolution microscopic analyses showed that the chromosome axis is regionally separated in hypomorphic Stag3 mutants and Smc1 β KOs, in which REC8‐cohesin levels are partly reduced (Agostinho, Manneberg, Schendel, Hernandez‐Hernandez, & Kouznetsova, ; Fukuda et al., ; Ishiguro & Watanabe, ). Notably, illegitimate SCs are assembled between sister chromatids at the REC8 free “axial opening” regions in these mutants (Agostinho et al., ; Ishiguro & Watanabe, ), as has also been shown in Rec8 KOs (Bannister et al., ; Xu et al., ). Thus, REC8 protects the chromosome axis from local “axial opening” and illegitimate SC assembly between sister chromatids (Figure b).…”
Section: Sister Chromatid Cohesion During Meiosissupporting
confidence: 52%
“…COs) along diplotene chromosomes, as illustrated for grasshopper and mouse (14,51,52). Moreover, a recent study using super-resolution microscopy in mouse meiocytes suggests that Rec8 prevents local separation of sister chromatid axes and illegitimate SC assembly (53,54). Studies of Sordaria prophase chromosomes further show that WT chromosomes exhibit axis splitting and loss of axis integrity specifically at CO sites and that this tendency is exaggerated when Rec8 is absent (14).…”
Section: Discussionmentioning
confidence: 99%
“…The DSB repair defect may be due to a failure to form chromosome axes. Cohesin has been identified as a part of meiotic chromosome axes (Klein et al 1999 ; Novak et al 2008 ) and is required for SC assembly (Hopkins et al 2014 ; Fukuda et al 2014 ; Ishiguro and Watanabe 2016 ). Rec8 is also a key component of linear elements in Schizosaccharomyces pombe , which does not have a canonical SC structure (Molnar et al 1995 ; Loidl 2006 ; Ding et al 2016 ).…”
Section: Resultsmentioning
confidence: 99%